The complexity of Rhipicephalus (Boophilus) microplus genome characterised through detailed analysis of two BAC clones - Valle Manuel; Morgan Jess A T; Lew-Tabor Ala E; Moolhuijzen Paula M; Peterson Daniel G; Dowd Scot E; Guerrero Felix D; Bellgard Matthew I; Appels Rudi (BMC Research Notes, 2011)
Abstract Background Rhipicephalus (Boophilus) microplus (Rmi) a major cattle ectoparasite and tick borne disease vector, impacts on animal welfare and industry productivity. In arthropod research there is an absence of a complete Chelicerate genome, which includes ticks, mites, spiders, scorpions and crustaceans. Model arthropod genomes such as Drosophila and Anopheles are too taxonomically distant for a reference in tick genomic sequence analysis. This study focuses on the de-novo assembly of two R. microplus BAC sequences from the understudied R microplus genome. Based on available R. microplus sequenced resources and comparative analysis, tick genomic structure and functional predictions identify complex gene structures and genomic targets expressed during tick-cattle interaction. Results In our BAC analyses we have assembled, using the correct positioning of BAC end sequences and transcript sequences, two challenging genomic regions. Cot DNA fractions compared to the BAC sequences confirmed a highly repetitive BAC sequence BM-012-E08 and a low repetitive BAC sequence BM-005-G14 which was gene rich and contained short interspersed elements (SINEs). Based directly on the BAC and Cot data comparisons, the genome wide frequency of the SINE Ruka element was estimated. Using a conservative approach to the assembly of the highly repetitive BM-012-E08, the sequence was de-convoluted into three repeat units, each unit containing an 18S, 5.8S and 28S ribosomal RNA (rRNA) encoding gene sequence (rDNA), related internal transcribed spacer and complex intergenic region. In the low repetitive BM-005-G14, a novel gene complex was found between to 2 genes on the same strand. Nested in the second intron of a large 9 Kb papilin gene was a helicase gene. This helicase overlapped in two exonic regions with the papilin. Both these genes were shown expressed in different tick life stage important in ectoparasite interaction with the host. Tick specific sequence differences were also determined for the papilin gene and the protein binding sites of the 18S subunit in a comparison to Bos taurus. Conclusion In the absence of a sequenced reference genome we have assembled two complex BAC sequences, characterised novel gene structure that was confirmed by gene expression and sequencing analyses. This is the first report to provide evidence for 2 eukaryotic genes with exon regions that overlap on the same strand, the first to describe Rhipicephalinae papilin, and the first to report the complete ribosomal DNA repeated unit sequence structure for ticks. The Cot data estimation of genome wide sequence frequency means this research will underpin future efforts for genome sequencing and assembly of the R. microplus genome.